Rapid platelet inhibition after a single capsule of Aggrenox®: Challenging a conventional full‐dose aspirin antiplatelet advantage? - Serebruany, Victor L.; Malinin, Alex I.; Sane, David C. (American journal of hematology, 2003)
Aggrenox® is a novel combination of 25 mg of aspirin with 200 mg of sustained release dipyridamole. In a recent large trial (ESPS‐2), Aggrenox® was twice as effective for secondary stroke prevention as either aspirin or dipyridamole alone, suggesting superior platelet inhibition for combination therapy. We sought to compare the time course of platelet inhibition with Aggrenox® compared with escalating doses of non‐enteric coated aspirin. Data from 10 healthy volunteers were analyzed. Fasting subjects sequentially ingested aspirin in the following order: 325 mg, 81 mg, 25 mg, and then one pill of Aggrenox® after a 3‐week interval for aspirin washout. Platelet function was assessed at baseline, 15, 30, 60, and 120 min post‐medication with 5 μM epinephrine and 5 μM ADP using conventional aggregometry. Aspirin provided significant (P < 0.01) reduction of platelet aggregation at 15 min post 325 mg, 30 min post 81 mg, and unexpectedly within 60 min after taking 25 mg of aspirin. A single pill of Aggrenox® also inhibited platelet aggregation within 1 hr after administration. Aspirin inhibits platelets remarkably fast. Both Aggrenox® and a matching dose of aspirin (25 mg) exhibit significant antiplatelet properties within 60 min after ingestion. These findings could be relevant for the optimal balance between the reduction of vascular events via sufficient and rapid platelet inhibition and low risk of bleeding complications associated with the Aggrenox® therapy. Am. J. Hematol. 72:280–281, 2003. © 2003 Wiley‐Liss, Inc.